Early proterozoic tectonothermal event south of the red river shear zone in Vietnam: first evidence from ... dating of single grain hornblende - Tran Ngoc Nam, Hironobu Hyodo, Tetsumaru Itaya (H. : ĐHQGHN, 2017)
tr. 26-34